Air pollution perception among the residents and medical practitioners of an industrial cluster in a developing country - S. Jawahar Saud; Anshu George Zacharias; Abinaya Sekar; B. V. Binoy; George Kuttiparichel Varghese; Aswathy Erat Valsan (Discover Environment)
Abstract Public perception on pollution and associated risks are important to plan and implement environmental health management programmes. The study was carried out to understand the perception of the residents near an industrial cluster on air pollution and its health impacts through a questionnaire survey. The survey included 28 questions across three areas: demography, general environment, and air pollution. To evaluate the perception of residents on their health vis-à-vis their actual health conditions, the medical practitioners working in the area were also interviewed. The association between the responses and the different demographic attributes of the respondents were explored using descriptive statistics. The study revealed that age had a significant influence on the perception of pollution, while gender, educational qualification, and length of residence had no significant influence. Based on the information shared by the medical practitioners, it is found that more than 100 residents approach them every day for conditions attributable to air pollution. The long-term environmental risk due to pollution among residents was rated 7 or above on a scale of 1 to 10 by the medical professionals. The PM2.5 concentration monitored continuously at two locations within the residential area covering the period of survey showed that the mean values exceeded the levels prescribed by National Ambient Air Quality Standards. In spite of the negative perception and poor health conditions, there have been no major corrective interventions by the concerned authorities. The study highlights the proactive role a government should play for protecting the health of citizens. Graphical Abstract